Systematic Literature Review: The Utilization of Social Media in Learning to Increase Student Engagement - M. Hadinuddin; Hamsi Mansur; Agus Salim (Publikasi Indonesia, 2025)
Education is a fundamental process that plays an important role in shaping quality individuals. In today's digital era, the integration of technology in education is important to create an interactive and dynamic learning environment. However, there are still many teachers who use conventional methods that make student engagement low. Student engagement is a key factor in learning success, involving cognitive, affective, and behavioral aspects. Social media, which has become an integral part of daily life, offers great potential to increase student engagement in learning. This research aims to explore the use of social media as a learning medium in increasing student engagement. Using the Systematic Literature Review (SLR) approach, this study examines literature related to the use of social media such as Facebook, YouTube, and WhatsApp in various educational contexts. The results of the study show that social media can increase student interaction, collaboration, and learning motivation. Teachers' wise and directed use of social media, as well as support from educational institutions, can enrich students' learning experiences and encourage their active engagement. This research makes a significant contribution to the development of more effective learning media innovations in the digital era, as well as providing insights for educators and policymakers in designing learning strategies that are more efficient and in accordance with technological developments.